v.2 - Campbell, R.H.; Skinner, A.S. (London, 1988)
This reissued biography of Adam Smith, first published in 1982, presents both an intellectual and personal portrait of the man. It is not intended as a full-scale scholarly biography burdened with heavy footnotes. Although written by two of the world's foremost authorities on Adam Smith, the book is intended as an accessible study of a great thinker and philosopher which will help to introduce the reader to both his ideas and his period.
Keywords: Sociological economics